2023
DOI: 10.1021/acs.jafc.2c06478
|View full text |Cite
|
Sign up to set email alerts
|

Four Different Structural Dietary Polyphenols, Especially Dihydromyricetin, Possess Superior Protective Effect on Ethanol-Induced ICE-6 and AML-12 Cytotoxicity: The Role of CYP2E1 and Keap1-Nrf2 Pathways

Abstract: Polyphenols have received attention as dietary supplements for the relief of alcoholic liver disease (ALD) due to various bioactivities. Ethanol-induced rat small intestinal epithelial cell 6 (IEC-6) and alpha mouse liver 12 (AML-12) cell models were pretreated with four dietary polyphenols with different structures to explore their effects on cytotoxicity and potential protective mechanisms. The results showed that polyphenols had potential functions to inhibit ethanol-induced AML-12 and IEC-6 cell damage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…There are a lot of unsaturated fatty acids in soybean oil emulsion. Hydrogen peroxide and malondialdehyde were easily produced by oil oxidation 33 . With the increase in storage days, the pH had a strong influence on the peroxide value and TBARS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a lot of unsaturated fatty acids in soybean oil emulsion. Hydrogen peroxide and malondialdehyde were easily produced by oil oxidation 33 . With the increase in storage days, the pH had a strong influence on the peroxide value and TBARS.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide and malondialdehyde were easily produced by oil oxidation. 33 With the increase in storage days, the pH had a strong influence on the peroxide value and TBARS. The peroxide values of emulsion at pH 6, 7 and 8 were significantly lower than those at pH 2.5 (P < 0.05).…”
Section: Lipid Oxidationmentioning
confidence: 98%
“…Alcohol is one of the most common causes of end-stage liver disease. In addition to alcoholic liver disease (ALD), more than 50% of patients with other liver diseases (including hepatitis C, nonalcoholic fatty liver disease (NAFLD) and hemochromatosis may also be associated with a large amount of alcohol intake. , Because of the dangers of excessive drinking, the alcohol consumption patterns in various regions of the world have changed. The average alcohol consumption in many European countries was decreasing, whereas the per capita alcohol consumption in Asian countries (e.g., China, India, and Vietnam) and many sub-Saharan African countries were increasing .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in our group have shown that pretreatment with chlorogenic acid (CHL), dihydromyricetin (DMY), apigenin (API), and phloretin (PHL) could protect ethanolinduced cytotoxicity of IEC-6 cells and AMI-12 cells. 13 Lacticaseibacillus rhamnosus (L. rhamnosus) 1.0320 has antiinflammatory, immune-enhancing, and intestinal microbiotaregulating biological activities. 14,15 Meanwhile, appropriate concentrations of CHL, DMY, API, and PHL were found to promote the growth and bacteriocin secretion of L. rhamnosus 1.0320.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies in our group have shown that pretreatment with chlorogenic acid (CHL), dihydromyricetin (DMY), apigenin (API), and phloretin (PHL) could protect ethanol-induced cytotoxicity of IEC-6 cells and AMI-12 cells Lacticaseibacillus rhamnosus (L.…”
Section: Introductionmentioning
confidence: 99%